Symptomatic Cerebral Vasospasm after Spontaneous Subarachnoid Hemorrhage: Comparison of Single and Multiple Intra-arterial Treatment with Respect to the Functional Outcome - Neumann, Alexander; Ditz, Claudia; Schacht, Hannes; Aulmann, Linda; Tronnier, Volker Martin; Schramm, Peter; Küchler, Jan Nils (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective In cases of spontaneous subarachnoid hemorrhage (sSAH) and symptomatic cerebral vasospasm (sCVS), multiple intra-arterial treatments (IATs) can be potentially useful for the functional outcome, even if the prognosis is initially poor. But the actual influence of the number of IATs has yet to be clarified. We wanted to assess if there are differences in the functional outcome between patients with a singular IAT and multiple IATs for sCVS after sSAH.Methods In a single-center study, 405 consecutive patients with nontraumatic SAH were analyzed retrospectively. A total of 126 developed sCVS, and 86 received IAT (32 singular and 54 multiple, i.e., more than one) with nimodipine with or without percutaneous transluminal angioplasty (PTA). Both groups were compared for demographic data, initial treatment (clipping or endovascular), and initial grading (World Federation of Neurosurgical Societies/Fisher classification, intraventricular hemorrhage, and intracerebral hemorrhage). The modified Rankin Scale (mRS) was used to assess functional outcome at the time of discharge and after 3 and 6 months. The development of CVS-associated infarction was assessed by computed tomography (CT). Categorical variables of the patient groups were analyzed in contingency tables using the Fisher exact test, chi-square test, and the Mann-Whitney U test. Statistical significance was accepted at p < 0.05.Results Patient groups with singular and multiple IATs were comparable concerning demographic data and initial grading. At the end of follow-up after 6 months, both groups showed comparable functional outcomes. A favorable outcome (mRS: 0–3) was observed in 14 of 26 patients (53.9%) with a single IAT and for 29 of 49 patients (59.2%) with multiple IATs. An unfavorable outcome (mRS: 4–6) occurred in 12 of 26 patients (46.1%) with a single IAT and for 20 of 49 patients (40.8%) with multiple IATs (p = 0.420). In the group with a single IAT, 22 of 32 patients (68.8%) developed CVS-associated infarction; 32 of 54 patients (59.3%) showed brain infarcts after multiple IATs (p = 0.259).Conclusion For patients with sCVS after sSAH, multiple IATs (nimodipine with or without additional PTA) can be applied safely because no significant differences in functional outcome were observed compared with a singular IAT. We conclude that patients should be treated repeatedly if vasospasm reoccurs.
Keywords: subarachnoid hemorrhage; cerebral vasospasm; nimodipine; endovascular treatment; delayed cerebral ischemia